2019
DOI: 10.12707/riv19022
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Brazilian version of the Functional Activities Questionnaire in the screening of dementia

Abstract: Background: Instruments for measuring functional disability of the elderly, such as the Functional Activities Questionnaire, can be used for the detection and prediction of dementia. Objective: To evaluate the accuracy of the Brazilian version of the Functional Activities Questionnaire (FAQ-BR) in dementia screening. Methodology: Cross-sectional study with 265 elderly and their respective informants. The performance of the FAQ-BR was compared to the clinical diagnosis of dementia and their score compared to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Both Jomar, et al [20] (AUC: .797) and [22] (AUC: .864) provided diagnostic accuracy measures. Jomar, et al [20] reported a sensitivity of 80%, specificity of 72%, positive predictive value of 68.7% and negative predictive value of 82.4% with a cut-off score of 14. Aprahamian, et al [22] used a cut-off of 11.5, showing a sensitivity of 85.3% and specificity of 76.5%.…”
Section: Functional Activities Questionnaire (Faq)mentioning
confidence: 96%
See 4 more Smart Citations
“…Both Jomar, et al [20] (AUC: .797) and [22] (AUC: .864) provided diagnostic accuracy measures. Jomar, et al [20] reported a sensitivity of 80%, specificity of 72%, positive predictive value of 68.7% and negative predictive value of 82.4% with a cut-off score of 14. Aprahamian, et al [22] used a cut-off of 11.5, showing a sensitivity of 85.3% and specificity of 76.5%.…”
Section: Functional Activities Questionnaire (Faq)mentioning
confidence: 96%
“…For Sanchez, et al [21] and Jomar, et al [20], 75% and 85.7% of informants had 9+ years of education, while Aprahamian, et al [22]'s sample were 100% illiterate.…”
Section: Functional Activities Questionnaire (Faq)mentioning
confidence: 99%
See 3 more Smart Citations